Recent trends in ergodic theory and dynamical systems: international conference in honor of S.G. Dani's 65th birthday, December 26--29, 2012, Vadodara, India - Bhattacharya, Siddhartha (Contemporary mathematics, 2015)
This volume contains the proceedings of the International Conference on Recent Trends in Ergodic Theory and Dynamical Systems, in honor of S. G. Dani's 65th Birthday, held December 26-29, 2012, in Vadodara, India.This volume covers many topics of ergodic theory, dynamical systems, number theory and probability measures on groups. Included are papers on Teichmuller dynamics, Diophantine approximation, iterated function systems, random walks and algebraic dynamical systems, as well as two surveys on the work of S. G. Dani.